هەلویستێ بریتانیا ژ شەرێ ئیران و عێراقێ ((1988-1980 - MIRO, DILEN ADEEB M. SALIH; MOHAMAD, SHIRZAD ZAKARIA (Journal of Duhok University, 2023)
The alterations that transpired within the Arabian Gulf in the late 1970s had a substantial impact on regional dynamics, particularly following the Islamic Revolution in Iran and its endeavors to disseminate its ideologies. This influence reverberated across neighboring nations, most notably Iraq. Concurrently, the disparities among these states were exacerbated, notably between Iran and Iraq. These divergences culminated in a major conflict, namely the Iran-Iraq War spanning from 1980 to 1988, particularly considering their interests becoming entangled with those of global powers such as Britain. Simultaneously, Britain sought to exert influence over the course of the war, albeit in a manner consistent with its regional policies, further compounded by its aspiration to maintain a neutral stance while exerting a direct impact.In this context, this study seeks to delineate the position of Britain within the context of the Iran-Iraq War, particularly concerning the political and diplomatic influences aimed at bolstering the faction favored by Britain. Moreover, it aims to illustrate that the Iran-Iraq War serves as an exemplar of numerous other conflicts in the Middle East, precipitated by the strategies of dominant states, notably Britain. This is because the British stance had the capability to intertwine the threads of the war with its multifarious objectives on several occasions, whether by altering the course of the conflict or by reinforcing the side it favored in the war. In addition to elucidating the criteria of the war and the entry of forces from Iran and Iraq, these actions ultimately posed a threat to the political equations envisaged by Britain within its strategic plans.